IMPLEMENTASI MANAJEMEN PEMBELAJARAN DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DI UPTD SDN 399 SIWA - Ridhah Rachman; H. Darmawan; Besse Herlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of learning management in improving student academic achievement at UPTD SDN 399 Siwa and to identify its supporting and inhibiting factors. The study employs a qualitative approach using field research. Data were collected through observation, interviews, and documentation. Data analysis utilized the Miles and Huberman model, which includes data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of learning management has been carried out through the stages of planning, organizing, implementing, and evaluating learning, which have proceeded quite well and contributed to the improvement of student academic achievement. The main supporting factors include the principal’s participatory leadership, teacher commitment, and a strong culture of cooperation. The inhibiting factors include limited facilities and infrastructure, teachers’ administrative workload, and differences in student abilities. Therefore, enhancing teachers’ competencies and providing adequate learning facilities are necessary to optimize student academic achievement.